Creation and Use of Vertical Gardening in the Interior of Apartments - Erkinovna, Karimova Dilnoza (International Journal on Integrated Education, 2023)
Man has always tried to surround himself with nature. Even in the era of total commitment to minimalism, the trend for natural materials has not gone into decline, but, on the contrary, has developed into a completely new direction in space decor. His name is eco-interior, or vertical gardening.